Anthropic effects on pollinators in the southernmost limits of subtropical dry forests - Aguilar, Ramiro (2017)
Human activities are dominant drivers of current biodiversity changes throughout the world. Land use practices such as deforestation, grazing, and agriculture affect ecosystem structure and functioning and regional climate. The southern most limits of subtropical dry forests have experienced the highest rates of deforestation worldwide over the past decades, and such landscape changes can alter plant-pollinator interactions in different ways. Animal pollinators are responsible for the sexual reproduction of 80% of angiosperms and also play a key role in fruit/seed production of domesticated species and in the reproduction of many useful wild species. Due to the essential ecosystem services provided by animal pollinators it is particularly important to learn about their dynamics in such changing environments. Here we assess pollinator richness and abundance in different anthropic scenarios: i) a gradient of habitat fragmentation landscapes, ii) unburned, high and low fire frequency sites, and iii) a gradient of agricultural intensification. Habitat fragmentation strongly reduced richness and abundance of Lepidoptera and Diptera and small solitary bees. More mobile pollinators such as hummingbirds, Bombus spp. however, showed no changes. Apis mellifera, showed an increased in relative abundance in smaller habitat fragments. Fire frequency also elicited species-specific responses of pollinators. Bombus spp. were equally abundant across sites whereas other pollinators such as Megachile sp., Notanthidium sp., Trimeria sp. were either reduced in abundance or absent. We discuss the implications of these findings for the reproduction of native plants species in ubiquitous human-altered landscapes.